A task development process: The case of fourth grade introduction to matter unit - (:unkn) unknown (Sakarya University, 2016)
Learning is affected from individual characteristics, learning objectives, and appropriate construction of learning environments. Learning tasks that are designed in educational environments play influential roles on students’ learning. The purpose of the current study was to develop fourth-grade science class tasks for Introduction to Matter Unit, using brain-based learning model and evaluate those tasks in the framework of brain-based learning principles. First, based on the learning objectives of the selected unit, several tasks were prepared. Then, those tasks were presented to the experts in the field of education to obtain information related to the utilities of each task in terms of learning objectives, developmental appropriateness, prior knowledge, time management efficiency, classroom organization, teacher-student roles, task difficulty, and material appropriateness. The procedural information provided by the experts was evaluated using Lawshe (1975) technique. The tasks were also implemented in a fourth-grade classroom. The results showed that the tasks are valid and compatible with the task design principles. The procedures used in this study are expected to contribute to the task development procedures in science lessons and other branches. It is also expected that the developed tasks will be in use of the researchers in the field of science education as well as the science and elementary school teachers. © The Turkish Online Journal of Educational Technology.
Keywords: Brain-based learning; Elementary school; Lawshe technique; Science lesson; Task development